1997
DOI: 10.1002/anie.199725111
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Polyrotaxanes from Stilbene Polymers and Cyclodextrins

Abstract: COMMUNICATIONS mononuclear fragment [Eq. (2)] should be competitive with dimerization to form [CU,L,]~+. For neocuproine, this is a highly favorable process and is only slightly less propitious for L'. Formation of the 1/2 complex is not so auspicious with L2, presumably because of steric crowding, and there is a serious drop in stability constant for this step. Metallohelicate assembly, following coordination of a second copper(1) center [Eq. (3)], is considerably easier with the more flexible bipyridylbased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…On the contrary, Wenz and his co-workers (112) reported that the linear polymer with stilbene units formed hetero polypseudorotaxanes with β-and γ-CD by adding stilbene. Moreover, they successfully obtained interlocked hetero polyrotaxanes with βand γ-CD by photoirradiation (112). Tetraphenylcyclobutane blocking groups along the polymer main chain have been formed by UV irradiation in the presence of β-and γ-CDs (Fig.…”
Section: Molecular Tubesmentioning
confidence: 97%
“…On the contrary, Wenz and his co-workers (112) reported that the linear polymer with stilbene units formed hetero polypseudorotaxanes with β-and γ-CD by adding stilbene. Moreover, they successfully obtained interlocked hetero polyrotaxanes with βand γ-CD by photoirradiation (112). Tetraphenylcyclobutane blocking groups along the polymer main chain have been formed by UV irradiation in the presence of β-and γ-CDs (Fig.…”
Section: Molecular Tubesmentioning
confidence: 97%
“…However, several problems have remained, e.g., how to control and read molecular motions. Shigekawa and Komiyama et al have nicely demonstrated that the selected a-cyclodextrin ring(s) of one of Harada s polyrotaxanes is(are) reversibly shuttled using scanning tunneling microscope (STM) technique [117]. The group showed three modes of shuttle manipulation, i.e., simple shuttling of a ring, pair-shuttling of two adjacent rings, and bending.…”
Section: Molecular Abacusmentioning
confidence: 97%
“…The solubility of the host/ guest complex in water is due to a partial coverage of the polymer chain by the host; the cyclodextrin rings preferably occupy the alkyl segments rather than the poly(oxyethylene) segments [127]. An interesting photochemical capping method with stilbene segments of a stilbene copolymer-based rotaxane was reported [128]. Poly(azomethynes) photoconductors have been included in -or -CyD and capped with N-butyl carbazole [129].…”
Section: Physical Entrapment In Different Polymeric Chainsmentioning
confidence: 99%